2015
DOI: 10.3109/10641963.2014.995801
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific associations of sleep duration with uncontrolled blood pressure in middle-aged patients

Abstract: Modest associations between short sleep duration and uncontrolled hypertension were seen in middle-aged women but not in men in the hypertensive population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Results from the Whitehall II Cohort Study showed that compared with 7 hours of sleep, short duration of sleep (5 hours per night) was associated with a higher risk of hypertension among women with an inverse linear trend across decreasing hours of sleep while no association was detected in men 26. In a cross-sectional survey conducted among patients with hypertension in the hypertensive outpatient clinic of Anzhen Hospital and a community hospital in Beijing, China, researchers showed a modest association between short sleep duration and uncontrolled hypertension in middle-aged women but not in men 27. There may be two possible reasons that may explain the sex difference in the correlation between sleep duration and hypertension.…”
Section: Discussionmentioning
confidence: 97%
“…Results from the Whitehall II Cohort Study showed that compared with 7 hours of sleep, short duration of sleep (5 hours per night) was associated with a higher risk of hypertension among women with an inverse linear trend across decreasing hours of sleep while no association was detected in men 26. In a cross-sectional survey conducted among patients with hypertension in the hypertensive outpatient clinic of Anzhen Hospital and a community hospital in Beijing, China, researchers showed a modest association between short sleep duration and uncontrolled hypertension in middle-aged women but not in men 27. There may be two possible reasons that may explain the sex difference in the correlation between sleep duration and hypertension.…”
Section: Discussionmentioning
confidence: 97%
“…The current study showed that those with a short sleep duration had a higher risk of uncontrolled SBP. Zuo et al 21) reported that sleep for >7…”
Section: Discussionmentioning
confidence: 99%
“…22 Similarly in 2 Chinese studies, short sleep duration was associated with higher SBP and DBP and risk of hypertension in females only. 25,26 These associations were particularly strong among early middle-age females (ages 35–44) in whom sleep duration <6 h/night vs. 7–8 h/night increased risk of hypertension by 77% ( OR: 1.77; 95% CI: 1.02–2.78). 25…”
Section: Sleep and Cardiometabolic Risk Factorsmentioning
confidence: 99%
“…More-recent studies in this area have been conducted primarily within Asian populations and have reported conflicting results. [22][23][24][25][26] In a cross-sectional analysis within the China Health and Retirement Longitudinal Study, compared with the reference group ( ‡ 7 h/night and <8 h/night), the groups who had <6 h/night and ‡6 h/night and <7 h/night had a 68%-69% higher risk of hypertension (OR: 1.68; 95% CI: 1.17-2.42 and OR: 1.69; 95% CI: 1.11-2.59, respectively) in middle-age men but not women. 24 Similarly in a crosssectional study of Korean women, null associations were reported between sleep duration and BP.…”
Section: Sleep and Cardiometabolic Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation